2021
DOI: 10.1186/s12974-021-02133-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dipeptidyl peptidase IV on disease-associated microglia phenotypic transformation in epilepsy

Abstract: Background Accumulating evidence suggests that disease-associated microglia (DAM), a recently discovered subset of microglia, plays a protective role in neurological diseases. Targeting DAM phenotypic transformation may provide new therapeutic options. However, the relationship between DAM and epilepsy remains unknown. Methods Analysis of public RNA-sequencing data revealed predisposing factors (such as dipeptidyl peptidase IV; DPP4) for epilepsy r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…The inactive NF-κB signaling pathway induced by the kappa opioid receptor (KOR) participated in suppressing neuronal injury and regulating microglial M2 polarization in epileptic rats [ 31 ]. Likewise, our laboratory also verified that sitagliptin (a DPP4 inhibitor) reduced the KA-induced activation of the NF-κB signaling pathway and suppressed the inflammatory response mediated by microglia in epilepsy [ 56 ]. Here, we found that PAP-1 inhibited the NF-κB signaling pathway, resulting in attenuation of both microglial activation and epilepsy severity.…”
Section: Discussionmentioning
confidence: 94%
“…The inactive NF-κB signaling pathway induced by the kappa opioid receptor (KOR) participated in suppressing neuronal injury and regulating microglial M2 polarization in epileptic rats [ 31 ]. Likewise, our laboratory also verified that sitagliptin (a DPP4 inhibitor) reduced the KA-induced activation of the NF-κB signaling pathway and suppressed the inflammatory response mediated by microglia in epilepsy [ 56 ]. Here, we found that PAP-1 inhibited the NF-κB signaling pathway, resulting in attenuation of both microglial activation and epilepsy severity.…”
Section: Discussionmentioning
confidence: 94%
“…Disease associated microglia (DAM) in neurodegenerative disease were CD11c positive, which participated in lipid metabolism and phagocytic pathways. DAM were considered to have the potential to restrict neurodegeneration [ 23 , 29 , 30 ]. Oligodendrocyte-supportive genes such as Spp1 and Igf1 were abundant in CD11c + microglia [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Sitagliptin, the first dipeptidyl-peptidase (DPP)-4 inhibitor, was approved and widely used as a glucose-lowering intervention for patients with type 2 diabetes [14]. Recently, more studies have reported the potential therapeutic effect of sitagliptin on other diseases including epilepsy, genital infections and COVID-19 [15][16][17]. Since studies have shown that DPP-4 is also expressed on the surface of macrophages [18,19], sitagliptin may have an influence on the biological function of macrophages, thus regulating the inflammatory diseases in which macrophage involved.…”
Section: Introductionmentioning
confidence: 99%